Tri-leafl et mitral valves – when lightning strikes thrice - van Rensburg, Annari; Pecoraro, Alfonso; Kyriakakis, Charles; Herbst, Philip; Doubell, Anton (SA Heart Journal, 2017)
Mitral valves are well known to be bi-leaflet structures with attachments from both leaflets (anterior and posterior) to both papillary muscles (anterolateral and posteromedial). Congenital abnormalities of the mitral valve, although well described, are quite rare. These abnormalities can involve either the leaflet (cleft mitral valve) or the subvalvular apparatus (parachute mitral valve) or even occur as accessory mitral valve tissue (accessory mitral valve leaflet). These can occur in isolation, or in association with other congenital abnormalities. A tri-leaflet mitral valve is a novel echocardiographic finding that has only been described in 6 patients in 4 different case reports.(1-4) We report on 3 patients recently found to have trileaflet mitral valves in the setting of atrioventricular concordance and normal offset of the AV valves at our out-patient clinic.